Investigating Spectral Red Shift Mechanism of Fluorescent Chromophores Using Time-Dependent Density Functional Theory (Journal of Atomic and Molecular Sciences, 2022)
Several fluorescent protein fluorophores with regular substitution were investigatedin gas phase using TDDFT with long range corrected functional. Absorptionand emission of both neutral and anionic chromophore states were calculated.The spectral shift amplitudes of calculation are in good agreement with experiment.The further intramolecular charge transfer process analysis show that conjugated area,charge transfer number/distance and transfer efficiency can affect spectral shift. Specially,the "N" atom with lone pair electrons of conjugated ring has an important influenceon charge transfer process, and the conjugated length between hydroxyl andbridge bond only impact the anionic spectral shift. Our results about fluorescent chromophorespectral red shift mechanism do provide positive clues on new experimentalfar-red fluorescent protein designing.